Digital Literacy Practices and Sustainable Development Goals 4: Experiences of International Students in Indonesian Higher Education - Lestari Budianto; Slamet Setiawan; Pratiwi Retnaningdyah (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mojokerto, 2026)
Objective: The growing number of international students in Indonesia has highlighted the importance of digital literacy in supporting academic success and cross-cultural adaptation. As higher education institutions strive to contribute to the Sustainable Development Goals (SDGs), particularly SDG 4 (Quality Education), understanding how international students engage with digital literacy practices becomes increasingly relevant. Method: To explore the digital literacy practices of international students studying in Indonesia and examines their perceived contributions to sustainable and inclusive educational experiences. Employing a qualitative approach, data were collected through semi-structured interviews with international students enrolled in Indonesian higher education institutions. Result: The findings reveal that digital literacy practices support students in accessing academic resources, participating in online learning communities, developing intercultural communication skills, and navigating academic and social challenges in a foreign environment. Novelty: The study further demonstrates that digital literacy contributes to equitable access to learning opportunities and promotes inclusive educational participation, aligning with the objectives of SDG 4 and SDG 10 (Reduced Inequalities). These findings suggest that digital literacy should be recognized as a critical component of sustainable international education. Universities are encouraged to strengthen digital literacy support systems to enhance international students’ academic engagement and foster more inclusive learning environments.